The wage and employment consequences of ownership change - Amess, Kevin; Girma, Sourafel; Wright, Mike (Wiley, 2013)
This paper provides a comparative examination of the consequences of leveraged buyouts (LBOs) and corporate takeovers on employment growth and wage growth. Employing both difference-in-differences combined with propensity score matching and the control function approach, we find evidence that (i) wages remain unchanged after either a private equity (PE)-backed or non-PE-backed LBO, (ii) wages remain unchanged after an unrelated takeover and (iii) related takeovers have negative employment consequences, possibly because of rationalisation. Our evidence does not find strong support for intervention in the market for corporate control on the grounds of protecting employees' welfare.